The implementation of civic education learning in indonesia: a systematic literature review - Sakban, Abdul; Budimansyah, Dasim; Darmawan, Cecep; Syaifullah, Syaifullah (Universitas Tanjungpura, 2025)
This study examines the development of Civic Education learning in Indonesia in recent years, focusing on analyzing trends in academic publications related to this topic. Through a literature study approach, data was collected from 200 relevant articles drawn from journals, proceedings, theses, and other documents obtained through observation and analysis of documents using the Publish or Perish and Scopus Premium applications. The study's findings show an increase in the number of publications by 2024, reflecting the growing interest in the importance of Civic Education in the context of democratization and diversity in Indonesia. Despite fluctuations, Indonesia shows rapid research growth, although it still lags behind countries with stronger academic traditions, such as the United States and China. Civic Education learning in Indonesia is shifting towards a more transformative and inclusive approach, emphasizing social and contextual relevance. This approach prepares the younger generation to participate actively in democratic life. Therefore, it is essential for Civic Education learning in Indonesia to continue to be adapted to local social and cultural needs to form critical, caring, and responsible citizens. This research contributes to understanding the development of Civic Education in Indonesia. It serves as a reference for developing a curriculum more adaptive to socio-cultural dynamics